Mitochondrial uncoupling in the melanocortin system differentially regulates NPY and POMC neurons to promote weight-loss - Natalie Jane Michael; Stephanie Elise Simonds; Marco van den Top; Michael Alexander Cowley; David Spanswick (Elsevier, 2017)
Objective: The mitochondrial uncoupling agent 2,4-dinitrophenol (DNP), historically used as a treatment for obesity, is known to cross the blood-brain-barrier, but its effects on central neural circuits controlling body weight are largely unknown. As hypothalamic melanocortin neuropeptide Y/agouti-related protein (NPY/AgRP) and pro-opiomelanocortin (POMC) neurons represent key central regulators of food intake and energy expenditure we investigated the effects of DNP on these neurons, food intake and energy expenditure. Method: C57BL/6 and melanocortin-4 receptor (MC4R) knock-out mice were administered DNP intracerebroventricularly (ICV) and the metabolic changes were characterized. The specific role of NPY and POMC neurons and the ionic mechanisms mediating the effects of uncoupling were examined with in vitro electrophysiology performed on NPY hrGFP or POMC eGFP mice. Results: Here we show DNP-induced differential effects on melanocortin neurons including inhibiting orexigenic NPY and activating anorexigenic POMC neurons through independent ionic mechanisms coupled to mitochondrial function, consistent with an anorexigenic central effect. Central administration of DNP induced weight-loss, increased BAT thermogenesis and browning of white adipose tissue, and decreased food intake, effects that were absent in MC4R knock-out mice and blocked by the MC4R antagonist, AgRP. Conclusion: These data show a novel central anti-obesity mechanism of action of DNP and highlight the potential for selective melanocortin mitochondrial uncoupling to target metabolic disorders.